Synaptic plasticity and NO-cGMP-PKG signaling regulate pre- and postsynaptic alterations at rat lateral amygdala synapses following fear conditioning. - Kristie T Ota (Public Library of Science (PLoS), 2010)
In vertebrate models of synaptic plasticity, signaling via the putative "retrograde messenger" nitric oxide (NO) has been hypothesized to serve as a critical link between functional and structural alterations at pre- and postsynaptic sites. In the present study, we show that auditory Pavlovian fear conditioning is associated with significant and long-lasting increases in the expression of the postsynaptically-localized protein GluR1 and the presynaptically-localized proteins synaptophysin and synapsin in the lateral amygdala (LA) within 24 hrs following training. Further, we show that rats given intra-LA infusion of either the NR2B-selective antagonist Ifenprodil, the NOS inhibitor 7-Ni, or the PKG inhibitor Rp-8-Br-PET-cGMPS exhibit significant decreases in training-induced expression of GluR1, synaptophysin, and synapsin immunoreactivity in the LA, while those rats infused with the PKG activator 8-Br-cGMP exhibit a significant increase in these proteins in the LA. In contrast, rats given intra-LA infusion of the NO scavenger c-PTIO exhibit a significant decrease in synapsin and synaptophysin expression in the LA, but no significant impairment in the expression of GluR1. Finally, we show that intra-LA infusions of the ROCK inhibitor Y-27632 or the CaMKII inhibitor KN-93 impair training-induced expression of GluR1, synapsin, and synaptophysin in the LA. These findings suggest that the NO-cGMP-PKG, Rho/ROCK, and CaMKII signaling pathways regulate fear memory consolidation, in part, by promoting both pre- and post-synaptic alterations at LA synapses. They further suggest that synaptic plasticity in the LA during auditory fear conditioning promotes alterations at presynaptic sites via NO-driven "retrograde signaling".